The reports of the magicians and astrologers of Nineveh and Babylon in the British Museum: the original texts, printed in Cuneiform characters; edited with translations, notes, vocabulary, index, and an introduction - Thompson, R. Campbell (Luzac's Semitic text and translation series, 1900)
Vol. 1. The Cuneiform texts.- Vol. 2. English translations, vocabulary, etc.